The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1021/acs.jafc.6b04740
|View full text |Cite
|
Sign up to set email alerts
|

Ginger Extract-Loaded Solid Dispersion System with Enhanced Oral Absorption and Antihypothermic Action

Abstract: The aim of this study is to enhance the antihypothermic action of ginger extract (GE) employing a solid dispersion (SD) approach. The prepared SD of GE (GE/SD) was characterized in terms of physicochemical and pharmacokinetic properties. The antihypothermic action of GE samples was evaluated in a rat model of hypothermia. GE/SD exhibited improved dissolution behavior of the major active ingredients in GE, 6-gingerol (6G) and 8-gingerol (8G), with levels of dissolution 12- and 31-fold higher than that of GE, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…But no newly formed peaks were found, indicating that vinegar soaking had no significant effect on the substance of fresh ginger, only that some components were increased due to structural instability and the conversion of some components to another more stable and similar compound. For example, gingerols are chemically unstable due to the presence of β‐hydroxy keto group which is easy to dehydrate and form shogaols or gingerones (Sato et al, ). Other pungent compounds in ginger demonstrate similar structural features.…”
Section: Resultsmentioning
confidence: 99%
“…But no newly formed peaks were found, indicating that vinegar soaking had no significant effect on the substance of fresh ginger, only that some components were increased due to structural instability and the conversion of some components to another more stable and similar compound. For example, gingerols are chemically unstable due to the presence of β‐hydroxy keto group which is easy to dehydrate and form shogaols or gingerones (Sato et al, ). Other pungent compounds in ginger demonstrate similar structural features.…”
Section: Resultsmentioning
confidence: 99%
“…After administration, they are quickly absorbed, accumulate in many tissues, and are intensively metabolized, which is why they are excreted in the form of metabolites in bile and urine [135]. An increase in the absorption of compounds contained in ginger extract can be achieved using the solid dispersion method [136]. Another option is to use castor oil as a nanostructured lipid carrier, which improves the bioavailability of ginger extract [137].…”
Section: Gingermentioning
confidence: 99%
“…To eliminate this problem, studies focusing on new drug carrier systems containing gingerol are important. Several studies evaluated the utility of different carrier solutions for efficient delivery of ginger compounds ( Yu et al, 2011 ; Sato et al, 2017 ; Wang et al, 2018b ; Ogino et al, 2018 ). In vivo studies investigating tissue distribution have shown that 6-gingerol is distributed to the lungs, brain, heart, liver, and kidneys, with the highest concentration in the gastrointestinal tract.…”
Section: Introductionmentioning
confidence: 99%